The Use of Membrane Cellulose from Nata as a Filter of Pliek U Oil - . Faridah; . Elwina; . Nadia (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
The research has been carried out in the laboratory scale to create and assess the ability of membrane cellulose from nata. Nata was produced from coconut-water and nira aren with a ratio 100%: 0%, 0%:100% and 50%:50%, which fermented with the addition of sugar and without the addition of sugar. Acetobacter xylinumwas added in medium as starter. The fermentation process was be done at 5, 7 9 days. The objective of this research was to study the influence of membrane cellulose as filter for Pliek U oil. Pliek U oil was filtered through membrane cellulose. Pliek U oil which was resulted have a good quality than before. Where membrane cellulosehas been able to reduce Free Fatty Acid (FFA), the results showed that the use of membrane cellulose from nata significantly reducesFree Fatty Acid (FFA). The membrane cellulose from coconut-water and nira aren without the addition of sugarat 9 days was reduced Free Fatty Acid from 2,43 % to 1,2%. But for density and index bias of Pliek U oil does not reduced with using membrane cellulose